Activation of 5-HT1 receptor in lateral habenula impaired contextual fear memory and hippocampal LTP in rat. (23rd January 2022) - Gu, Jingsheng; Hou, Zhijie; Zhou, Xiaotao; Wang, Qinglei; Chen, Yanmei; Zhang, Jichuan
Highlights: Activation of 5-HT1 receptor in LHb impaired contextual fear memory in rats. Activation of 5-HT1 receptor in LHb impaired hippocampal synaptic plasticity in rats. Activation of 5-HT1 receptor in LHb increased anxiety- like behavior in rats. Abstract: Serotonin (5-hydroxytraptamine, 5-HT) is a neurotransmitter plays important roles in emotion and motivation. The action of 5-HT varies across nucleus and the receptor sub-types. Lateral habenula (LHb) in a brain area reciprocally connects with raphe nucleus and plays important roles in emotion and depression. In this study, we aimed to study the role of 5-HT1 receptor in LHb on fear learning. 15 min before or immediate after the fear conditioning, 5-Carboxyamidotrypamine maleate salt (5-CT), an agonist of 5-HT1 receptor, was bilaterally delivered into LHb (1 μg/μl, 1 μl/side) in rats. We found that activation of 5-HT1 receptor in LHb impaired the acquisition but not consolidation of fear memory in rats, which was accompanied by impaired long-term potentiation (LTP) and decreased phosphorylation of α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (AMPAR) subunit 1 (GluA1) at the Ser845 site in hippocampus. In addition, 5-CT decreased the time spent in center area of the open field and time spent in open arm in elevated plus maze. These results suggest that activation of 5-HT1 receptor in LHb impaired acquisition of hippocampal dependent fear memory and increased anxiety- like behavior in rats.